Group-based trajectories and predictors of adherence to physical distancing during the COVID-19 pandemic. Issue 12 (2nd December 2022) - MacNeil, Sasha; Deschênes, Sonya; Knäuper, Bärbel; Carrese-Chacra, Emily; Dialahy, Isaora Zefania; Suh, Sooyeon; Durif, Fabien; Gouin, Jean-Philippe
Abstract: Objective : This study sought to identify psychosocial predictors of trajectories of adherence to physical distancing alongside changes in public health measures during the COVID-19 pandemic. Design : A three-time point longitudinal survey during the first two waves of the COVID-19 pandemic. Methods : Participants ( N = 1003) completed self-report measures of adherence to physical distancing over an 8-month period at the start (T1) and end (T2) of the first wave of the pandemic, and the start of the second wave of the pandemic (T3). Participants also completed measures of their health beliefs related to the self and others, social norms, emotional distress, and sociodemographic characteristics. Results : Using group-based trajectory modeling, four trajectories of adherence to physical distancing emerged: a high-adherence trajectory, a slow-declining trajectory, a fluctuating trajectory, and a fast-declining trajectory. The most important psychosocial predictors of poorer adherence trajectories included perceptions of lower self-efficacy and higher barriers to adherence, as well as lower prosocial attitudes towards physical distancing. Conclusion : Public health messages targeting these factors may be most relevant to promote sustained adherence to physical distancing over time in the context of a pandemic.